How Employee Portal Contributes for the Intangible Assets Value Creation - Mendes, David; Romão, M. (IAMB 2013 - International Academy of Management and Business, 2013)
Today's increasingly business competition and the information technologies development led to huge corporate organizational changes and pulled intangible assets up in the value chain. Employees‘ skills, talent and know how, intellectual property, information, information systems, infrastructure, culture, teamwork capacity and other forms of non-physical assets are critical sources of value. But in order to generate value they must be integrated with each other and aligned with the objectives for the internal processes. This position paper addresses organization concerns related to value creation and change management and highlights the importance of visual representation of ?strategy? to provide an understanding on the cause-effect relationships that generate value, as well as providing top management and decision makers the information needed for a suitable top-down commitment and sponsorship – essential to perform appropriate change management and benefits realization. The paper presents a theoretical multi-tier framework that shows the path and flows of value-creation, the relationships between ?intangible assets? and the representation of ?enabling changes projects?. We‘ve combined Strategy Map and Benefits Dependency Network, resulting in a stronger framework to help organizations enhancing their strategy knowledge, to reduce the risk of projects failure, and to capture real value from their investments. This framework is being applied to an on-going Employee Portal case study, as a means to understand how a corporate employee portal contributes to the intangible assets value creation process.